PELAKSANAAN PERJANJIAN KONTRAK KERJA KONTRUKSI PEKERJAAN PEMBANGUNAN JALAN DAN JEMBATAN LINGKAR DALAM SELATAN BANJARMASIN ANTARA PT. DIKANU DENGAN DINAS PEKERJAAN UMUM BIDANG BINA MARGA PROVINSI KALIMANTAN SELATAN - , IRFANSYAH RIDHANI, Taufiq El Rahman, SH., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study aims to investigate the implementation of construction work contract in the construction of the ring road south Banjarmasin between PT. Dikanu with the Department of Public Work, Highways Maintenance Sector South Kalimantan The approach method used in this study is an empirical juridical approach, an approach method which refers to the rules and norms of the existing laws conducted by the researcher in which the researcher obtains empirical knowledge by having field research. The main data in this study is primary data obtained directly from research subjects. To complete the primary data, library research was also conducted. The research subjects consisted of 6 (six) respondents consisting of 2 (two) the auction committees, 2 (two) the companies and 2 (two) executive consultants. The data obtained were analyzed using descriptive approach and directed to deduce conclusion through actual facts. The results of this research consist of following explanations. First, the implementation of the construction work contract between the service provider and the service user is always subject to a change. This condition is related on the field condition when the work is performed